OSCILLATION OF THIRD ORDER DELAY DIFFERENTIAL EQUATION WITH SUBLINEAR NEUTRAL TERM - RAMA*, RENU (International Journal of Mathematical Archive, 2018)
The aim of this paper is to study the oscillatory and asymptotic behaviour of solutions of the equation....